Температурные и концентрационные зависимости подвижности носителей заряда в твердых растворах (PbS)1–x(Sm2S3)x - Hasanov, G. A.; Murguzov, М. І. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The temperature dependences of electrical conductivity, Hall coefficient, and charge carrier mobility (μH) have been investigated in cast and pressed samples of solid solutions (PbS)1–x(Sm2S3)x with x = 0–0.04. For pressed samples (x = 0.001–0.0016) in the temperature range 77–200 K, an anomalous exponential increase in μH is observed with increasing temperature, which is explained by the presence of energy barriers created by oxide films at grain boundaries. In the dependences of μH on Sm2S3 content in the composition range 0.1–0.16%, anomalies were detected that are associated with a concentration-induced phase transition of the percolation type.